MENENTUKAN FORMULA PREMI TAHUNAN TIDAK KONSTAN PADA ASURANSI JOINT LIFE - SUBADRA, I GEDE BAGUS PASEK; WIDANA, I NYOMAN; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2015)
The aim of this research was to determine the annual premium formula that turns on the joint life insurance. This formula uses the reference insurance contracts of the previous research Insurance Models for Joint Life and Last Survivor Benefits. The first step is to determine the value of mortality tables by using the Table Helligman-pollard. Furthermore, determining the value of a life annuity and single premium. The results of this research was formula to be affected by the changing premium ( ) with the increase and decrease in constant interest.
Keywords: The Annual Premium; The Annual Premium Turned; Joint Life Insurance; ?